Physical activity, television viewing time, and retinal microvascular caliber - Anuradha, S.; Healy, Genevieve; Dunstan, D.; Klein, R.; Klein, B.; Cotch, M.; Wong, T.; Owen, N. (2011)
Physical activities and sedentary behaviors are 2 broad classes of behavior that may be clearly distinguished from each other and have different patterns of determinants. The authors examined the associations of physical activity and television viewing time with retinal vascular caliber among US adults (n = 5,893) from 4 racial/ethnic groups in the Multi-Ethnic Study of Atherosclerosis (2002-2004) that included non-Hispanic whites, blacks, Hispanics, and Chinese. Physical activity and television viewing time were assessed by using a questionnaire, and vascular calibers (arteriolar and venular) were measured from digital retinal photographs. Those in the lowest quartile of physical activity had wider retinal venular caliber compared with those in the highest quartile in multivariate models adjusted for demographic, cardiovascular, behavioral, and inflammatory risk factors. This was noted in non-Hispanic whites and Hispanics but not in blacks or Chinese. For television viewing time, non-Hispanic whites (but not the other racial/ethnic groups) who were in the highest quartile of television viewing time had wider retinal venular caliber compared with those in the lowest quartile. No associations were noted with arteriolar caliber. Lower levels of physical activity (among non-Hispanic whites and Hispanics) and higher levels of television viewing time (among whites) are associated with wider retinal venules. © The Author 2011.